Union Strategies of Addressing Conflicts at the National University of Lesotho - Mojalefa, Mamoeletsi Limakatso (Business Management and Strategy, 2021)
This paper discusses the strategies that are used by the unions to address industrial conflict at the National university of Lesotho (NUL). Content analysis was undertaken to understand the interviewee’s responses and the NUL policy documents. The strategies are analyzed within the policy context, pre-industrial action, industrial action and post-industrial action. The study also shows that unions at the higher education institutions consult with other unions in the sector and, where other strategies have failed, they resort to either industrial action or legal process to resolve conflicts at the workplace. The findings further show that unions employ widespread communication between their members to share new development in the negotiation process. The findings reveal that strategies which unions normally adopt at NUL are: constant consultations and joint decision making, strikes/industrial action, work to rule, negotiations, collective bargaining, taking legal process and communication of possible ideas and solutions.